(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kalyuzhna T. H. Value priority of teacher and education. The valued priorities of modern teacher are considered in the article, bases of pedagogical axiology are marked as a base of the valued education. It is marked that the new model of Ukrainian pedagogical education must be based on Ukrainian national traditions, acquisitions of domestic pedagogic and critically intelligent experience of foreignness.